The Effect of Cognitive Behavioral Intervention Based on Self-Management on the Ability to Control Hallucinations in People with Schizophrenia - Sari, Dewi Keumala; Purba, Jenny Marlindawani; Sitohang, Nur Asnah (Jurnal Kesehatan, 2024)
Hallucinations are a common symptoms found in individuals with schizophrenia. These hallucination cause people with schizophrenia (PWS) to experience difficulty in controlling themselves. This has an impact on suicidal behavior, harming other people, and destroying the surrounding environment. Therefore, a cognitive behavioral intervention based on self-management is needed as a non-pharmacological therapy to help PWS control hallucinations. This study aims to identify the effect of cognitive behavioral interventions based on self-management in people with schizophrenia. This study uses a quasy-experimental two groups pretest-posttest design. The sample consists 78 inpatient respondents with schizophrenia, divided into two groups, 39 in the intervention group and 39 in control group. Technique sample in this study using purposive sampling. Research data collection uses a questionnaire instrument for the ability to control hallucinations. The data explained used statistics, such as descriptive, dependent, and independent t-tests. The research results show that there are changes in the ability to control hallucinations in the intervention group and control group before and after self-management-based cognitive behavioral intervention (p-value=0.001). There was a difference in the ability to control hallucinations between the intervention group with the control group after cognitive behavioral intervention based on self-management (p-value= 0.013). The cognitive behavioral intervention based on self-management can be used as an effective cessation intervention to improve the ability of PWS to control hallucinations so that they can optimize their function in carrying out daily activities.